Effect of profit quality on stock prices in manufacturing companies - Maharizy, Zizi; Yuliantika, Tya Yuliantika (Economy, Business, Finance, Accounting & Management Journal, 2025)
This study examines the effect of earnings quality on stock prices in manufacturing companies, with the aim of providing empirical evidence on how reliable and informative financial reporting influences market valuation. Earnings quality, defined as the extent to which reported earnings reflect a company’s true economic performance, is a critical factor in investment decision-making. Low-quality earnings, often influenced by aggressive accounting practices, can distort investors’ perceptions and lead to mispricing in capital markets. Using a sample of manufacturing companies listed on the Indonesia Stock Exchange over the 2018–2023 period, this research employs a quantitative approach with panel data regression analysis. Earnings quality is measured through accrual-based and real earnings management indicators, while stock prices are captured through year-end closing prices. Control variables include firm size, leverage, and growth opportunities. The results indicate that higher earnings quality has a significant positive effect on stock prices, suggesting that investors value transparent and sustainable earnings information. Conversely, firms with low earnings quality tend to experience weaker market valuations, reflecting reduced investor confidence. These findings highlight the importance of enhancing the credibility of financial reporting through robust accounting standards and effective corporate governance. The study contributes to the literature on capital market efficiency and offers practical implications for policymakers, investors, and corporate managers